POWER ELECTRONICS COURSES FOR THE NEW PARADIGMS OF THE ELECTRICAL SYSTEM - Pomilio, J. A. (2011)
This paper presents a historical perspective of the Power Electronics education that has lead to the present situation in which such technology is indispensable for the exploitation of almost all type of clean energy primary sources. Some academic initiatives in Brazil are here discussed focusing the institutions grouped in a CAPES-Pro-Engenharia program. The curricula aspects and innovations are presented, emphasizing the multidisciplinary character of this field of Power Electronics application.